Personality According To Sigmund Freud (Critical Response Worldview Perspective) - Muhammad Dhiaul Fikri; Amir Reza Kusuma (Feelings: Journal of Counseling and Psychology, 2025)
This paper will explain the features of Western epistemology that have contributed to the development of the discipline of modern psychology, specifically regarding the human personality in Freud's school of psychoanalysis. Modern Western epistemology model which is attached to logic-empiric and dualistic, causes the understanding of human personality to be less comprehensive. In this case the aspect of fitrah ruhiyyah which is the core of the Islamic teaching tradition becomes empty. By using the Islamic worldview approach, this simple study concludes a number of important points: The personality that Freud's formulation in the flow of psychoanalysis emphasizes that the sex or life instinct (libido) which works based on pleasure (Pleasure principle) is the main driving force of human personality. This point of view makes the object of study in the realm of psychology not holistic, because it is only limited to human biological (Jismiyyah) and psychological (Nafsiyyah) aspects. By emphasizing the somatic aspect alone, Freud's formulation of the human personality actually leaves a problem. The concept of personality, which should emphasize the aspect of fitrah ruhiyyah, is not made the core of the discussion. This problem of imbalance characterizes as well as characterizes all schools of modern psychology.